Predictors of maternal pertussis vaccination acceptance among pregnant women in Norway - Bo T. Hansen; Brita A. Winje; Jeanette Stålcrantz; Margrethe Greve-Isdahl (Taylor & Francis Group, 2024)
Maternal vaccination against pertussis is safe and provides effective protection against pertussis for the newborn, but the vaccine coverage rate remains generally low. Norway is currently planning for introduction of routine maternal pertussis vaccination. To assess maternal pertussis vaccination acceptance among pregnant Norwegian women, we surveyed women at 20-40 weeks gestation in 2019. Among the 1,148 pregnant women participating in this cross-sectional study, 73.8% reported they would accept pertussis vaccination during pregnancy if it was recommended, 6.9% would not accept and 19.2% were undecided. Predictors for low likelihood of accepting pertussis vaccination during pregnancy included low confidence in health authorities and in maternal pertussis vaccination safety and effectiveness, low awareness and adherence to influenza vaccination during pregnancy, and low awareness of pertussis vaccination. The major reasons reported for not accepting or being undecided about maternal pertussis vaccination were lack of information on vaccine safety for both mother and child. Most women reported that they would consult their general practitioner or a midwife for information if they were offered maternal pertussis vaccination. General practitioners and midwives were also regarded as the most trustworthy sources of information if the women were in doubt about accepting vaccination. We conclude that information addressing safety concerns and raising awareness about maternal pertussis vaccination could increase acceptance of maternal pertussis vaccination. Our findings highlight the pivotal role of the antenatal and primary health care services in providing such information to pregnant women.